Generic competences self-reported by Brazilian university students - Carvalho, Priscila Larangeira; Araújo, Fernanda Ribeiro de; Scachetti, Rodolfo Eduardo; Freire Seoane, María Jesús; Oliveira-Monteiro, Nancy Ramacciotti de (Education Policy Analysis Archives, 2021)
Although there is no standardization of the notion of competence and for the instruments used in its evaluation, generic competences are associated with employability, and understood as a composition of cognitive and practical abilities, behavioral and social skills, gathering individual characteristics and qualities required for activities of different professions. Education promotes the development of specific competences for the exercise of certain occupations, in addition to opportunities for increasing generic competences, which are also required in the labor market. This study targets to evaluate self-perception of the valuation of generic competences acquired in undergraduate students from nocturnal courses of Brazilian private university, according to area of knowledge and condition of being or not inserted in the labor market. 1,001 of these students were evaluated in the third year of their graduation, using the Generic Competences Scale. The highest value in the global sample was attributed to Responsibility at work, followed by Ethical commitment and, thirdly, by Capacity to learn. At the other end, of lesser value, were Capacity for organization and planning, Ability to manage information and Problem solving. These results were compared with data from other studies, in Latin America and Europe. <!--[if !supportLineBreakNewLine]--> <!--[endif]-->